Management of stenosis lesions during the period of endovascular treatment for acute ischemic stroke - Hong-xing HAN; Qi-yi ZHU; Jian GONG; Xian-jun WANG; Yun-yong LIU; Zhen-yu ZHAO; Hao WANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2017)
Objective To investigate the management of stenosis lesions during endovascular treatment for acute ischemic stroke. Methods A total of 36 acute ischemic stroke patients combined with intracranial/extracranial arterial stenosis were treated with endovascular treatment or bridging treatment. Time from aggravation on admission or in hospital stay to femoral artery puncture, from femoral arterypuncture to recanalization were recorded. Modified Thrombolysis in Cerebral Infarction (mTICI) was usedto assess the recanalization immediately after operation. Modified Rankin Scale (mRS) was used to evaluate prognosis at 90 d after operation. Occurrence rate of symptomatic intracranial hemorrhage and mortality were recorded. Results Among 36 patients, 13 patients (36.11%) underwent intravenous thrombolysis and then endovascular thrombectomy. In all patients, there were 21 (58.33%) with intracranial stenosis and 15 (41.67%) with extracranial stenosis, 16 (44.44%) with anterior circulation stenosis and 20 (55.56%) with posterior circulation stenosis. Stent thrombectomy was used in 25 patients (69.44% ), while balloon dilatation and/or stent implantation was used in 11 patients (30.56% ). For 21 patients with intracranial arterial stenosis, 4 were treated with balloon dilatation only, 9 with Wingspan self-expandable stents and 8 with Apollo balloon-expandable stents. Fifteen patients with extracranial arterial stenosis were treated with balloon dilatation and stent implantation. A total of 33 patients (91.67%) achieved recanalization (mTICI 2b-3 grade), 21 patients (58.33% ) had good outcomes (mRS ≤ 2 score), while symptomatic intracranial hemorrhage occurred in 2 patients (5.56%) and 5 (13.89%) died. There were no statistically significant differences in the rate of good prognosis, symptomatic intracranial hemorrhage and mortality between intracranial and extracranial arterial stenosis, anterior and posterior circulation stenosis (Fisher exact probability: P > 0.05, for all). Conclusions For acute ischemic stroke patients combined with intracranial/extracranial arterial stenosis, endovascular treatment is safe and effective.